Hubungan Hemoglobin Dengan Tingkat Motivasi Belajar Pada Siswa di SMA Mulia Pratama Medan - Rahmawati Karo-Karo; Mhd. Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Learning motivation has a very important role in the learning process, with high motivation it can help students to achieve brilliant achievements in learning.The purpose of this study was to determine the relationship between hemoglobin and the level of student learning motivation at SMA Mulia Pratama Medan.The method used quantitative methods with a cross sectional design. The population in this study was 50 students who were still actively taking lessons. The sampling technique in this research is Total Sampling. The instruments in this research used questionnaires and hemometers. The collected data was analyzed using the Spearman Rho test. The results of this study show that there is a relationship between hemoglobin and the level of learning motivation with a p value of 0.000 (p value < 0.05). The result of study research show that there is a relationship between hemoglobin and the level of learning motivation students at SMA Mulia Pratama. It is recommended for future researchers to add other variables such as student learning achievement, parenting patterns, as well as conducting research with different types of research, and research as consideration for further research.